Tutu and Havel say athletes have duty to speak up for human rights. (Tibetan Review: The Monthly Magazine on all Aspects of Tibet, 2008)
The article reports on the call of former Czech president Vaclav Havel and Nobel Peace laureate Desmond Tutu for the International Olympic Committee (IOC) to let athletes be aware of the suppression of liberties in China through an open letter. It notes that IOC should let Olympic athletes express freely their opinions. The open letter was signed by Chinese President Wei Jingsheng and European Parliament Vice-President Edward McMillan-Scott.